Analysis of the implementation of the scheduling and tracking project application at CV. Emporio architect - Pathni, Ida Ayu Wisma Anggaritha; Gunadi, I Gede Aris; Sunarya, I Made Gede (SEAN Institute, 2024)
CV. Emporio Architect make a Scheduling and Tracking Project application is created to help employee performance in scheduling a project. However, the implementation in the field had not met expectations, where each division made its own schedule and kept it individually, so that there was no transparency in the performance of the inter-divisional relay teams. This was because many divisions did not use the applications provided by the company. From the background description above, it is necessary to identify the factors that influence the use of Scheduling and Project Tracking applications on CV. Emporio Architect. The aim of this research is to analyze the implementation of the Scheduling and Tracking Project application by identifying factors that influence the use of the application using the TOE Framework research model and quantitative methods with data collection techniques through questionnaires, interviews and observation. The population in this study consisted of 58 respondents, and the data analysis was conducted using validity tests, reliability tests, multiple linear regression analysis, and hypothesis testing. The data testing was processed with the help of SPSS software. The research results identified that the variables of technology and organization did not significantly affect the implementation of the application, leading to the ineffectiveness of the application implementation at CV. Emporio Architect, as expected. However, the environmental variable had a significant influence according to the conditions at CV. Emporio Architect. The suggested recommendation is that the company improves from both technological and organizational aspects so it can be better at preparing for implementing scheduling and project tracking applications at CV. Emporio Architect.